Building structures - Ambrose, James E (Wiley, 1988)
A concise reference tool for the professional involved in the production of details for building construction, this abridgement of the classic Architectural Graphic Standards provides indispensable guidance on standardizing detail work, without having to create the needed details from scratch. An ideal "how to" manual for the working draftsperson, this convenient, portable edition covers general planning and design data, sitework, concrete, masonry, metals, wood, doors and windows, finishes, specialties, equipment, furnishings, special construction, energy design, historic preservation, and more.